INOVASI BISKUIT TOMAT DAN BAYAM DAN APLIKASI E- MONITORING GIZI PENTING - Febriansyah, Febriansyah; Oktavianus, Donny; Jannah, Syerina Raihatul (Jurnal Abdimas Bina Bangsa, 2024)
This program aims to provide nutritious food supplements for toddlers through the development of tomato and spinach biscuits (TOMYAM) and to assist *posyandu* (community health post) cadres in monitoring children's nutrition using the E-TingTing application in Aromantai Village. The methodology involved socialization on the importance of toddler nutrition, training in TOMYAM biscuit production, and the use of the E-TingTing application. The program provided tools such as biscuit-making equipment and smartphones for operating the app. The E-TingTing application was designed to digitally record and monitor children’s nutritional status. The results showed that cadres successfully learned how to produce TOMYAM biscuits and use the application effectively, making data recording and monitoring more manageable and enabling timely interventions. The program also increased parental involvement in their children’s nutrition and improved the cadres' skills in both biscuit production and digital health monitoring. In conclusion, the development of TOMYAM biscuits and the E-TingTing application enhanced the capacity of *posyandu* cadres to provide nutritious supplements and monitor children’s nutrition more efficiently. However, the program's sustainability requires continuous support, particularly in overcoming challenges related to technology and internet access in the region.